Rendimiento térmico y geometría de cubiertas en iglesias de San José de Cúcuta, Colombia (2024)
Understanding the thermal performance of architectural enclosures is fundamental due to its environmental, economic, social, and political implications worldwide. This study investigates the impact of roof geometry on the thermal performance of three churches in San José de Cúcuta, Colombia: The Cathedral of San José, the Church of Our Lady of Candelaria, and the Church of Our Lady of Carmen. The methodology is divided into four parts: configuration of simulation variables, simulation execution, data analysis, and thermal characterization of different types of roof enclosures. Conducting heat transfer simulations in ANSYS is based on previous research on solar incidence and heat transfer on church roof surfaces. The results highlight the importance of geometry in mitigating exterior and interior temperatures in warm climates such as that of San José de Cúcuta. This provides valuable information for architects and designers, enabling them to make informed decisions to optimize building thermal efficiency and improve occupant comfort, making this research valuable for architectural practice.